Hubungan Kecerdasan Interpersonal Dengan Sikap Belajar Fisika Siswa Kelas VII SMP Negeri 5 Angkola Timur - Simanjuntak, Mombang; Siregar, Sri Utami Kholilla Mora; Eni Sumanti (Yayasan Perguruan Kampus, 2024)
This study aims to determine the relationship between students' interpersonal intelligence with the attitude to study Physics in class VII students of SMP Negeri 5 Angkola Timur. The formulation of the problem in this study is whether there is a relationship between students' interpersonal intelligence and the attitude of learning Physics in class VII students of SMP Negeri 5 Angkola Timur?”. The sample in this study was class VII students of SMP Negeri 5 Angkola Timur with a total of 28 students. The instrument in this research is a questionnaire in measuring learning attitudes and interpersonal intelligence. This type of research is correlation research. Data analysis techniques use normality tests, homogeneity, linearity tests. Test the hypothesis using regression and correlation tests. The results showed that there was a positive and significant relationship between interpersonal intelligence and the learning attitudes of class VII students of SMP Negeri 5 Angkola Timur. with a significant 0.004 which means less than 0.05 there is a significant positive relationship between the interpersonal intelligence variable (X) and learning attitude (Y) with a high correlation criterion of 52.8%.